Diversification Analyzes The Concept Of Branding And Promotion To Company Performance - Alin Nesia; Gede Sri Darma (Universitas Pendidikan Nasional, 2015)
This research is madeto determine whethera particular concept ofbranding andpromotion, could help to improve the company’s marketing performance. Apart from twovariables, which are location and marketer, there is also promotion that could improvecompany’s marketing performance. These three are intervening variables to help thecompany’s performance.From the results of research conducted using questionnaire data obtained from 128respondents, which questionnaire results were tabulated using Microsoft excel and processedby the method of Statistics Structural Equation Model ( SEM ) with 20.0 Amos programshowed that the eight criteria Goodness of Fit, there are three criteria are met and onecriteria is marginal. The results obtained after one modifying. Followed by data processingbetween variables can be seen that between five variables studied, the most powerfullvariable is the variable effectiveness of strategy execution. Promotion variable is the variablewith the highest score after the missed intervening variable ( direct effect ).With these results , we can conclude that PT. Arkadena need a strong team with thestrong concept diversification branding and promotion that should be decided by a goodstrategy execution to supporting the companies performance.Keyword : Location, Promotion, Diversification, Branding, Marketer,Strategy Execution,Company Performance